(untitled) (Dhaka University Journal of Biological Sciences, 2013)
Effects of sodium fluoride (NaF) on Clarias batrachus in the aquarium at a sub lethal dose of 0, 15, 30, 40, 50 and 60 mg/l for a chronic exposure period of 120 days were evaluated. The histopathological alterations in different tissues from brain, gill and liver were examined in fishes showed abnormal behaviors. Such as rupture of hepatocytes, congestion, necrosis pyknosis, cellular infiltration, and degenerative changes. In case of liver, individualization of hepetocytes, mild necrosis, vacuolation, pyknosis and hemorrhage were observed. These results suggest that NaF affects severely on the tissues of the internal organs leading to threat of life and survival. Dhaka Univ. J. Biol. Sci. 22(1): 1-7, 2013 (January)